Analisis Faktor-Faktor Yang Mempengaruhi Jumlah Uang Beredar Di Indonesia Periode Januari 2012-Juli 2015 - Saputra, Nugraha Nur Adi, Didit Purnomo, SE., M.Si (2016)
Money Supply (JUB) is a problem in the long-term economy and dopengaruhi by various factors. This study was conducted to analyze the effect of inflation, interest rates, and foreign exchange reserves terhaadap the amount of money circulating in Indonesia. In this study using multiple linear regression analysis models Ordiary Keast Square (OLS). For purposes of analysis used secondary data such as time series data from January 2012-July 2015 that is data Indonesia in the money supply, inflation rates, interest rates, and foreign exchange reserves. Data obtained from Bank Indonesia (BI), the Central Statistics Agency (BPS), sources and other relevant sources. The results showed variable foreign exchange reserves and the Interest Rate, bersam both positive and significant impact on the Money Supply (JUB) with a probability value of 0.0057 and 0.0000. While variable rate nflasi berpengaruhsecara not significantly .terhadap the money supply in Indonesia with a probability value of 0.0637